Effect of Cationic Surfactant on the Kinetics of Oxidation of Propionaldehyde - Ahmad, Firoz; Abbas Siddiqui, M.; Singh, Ritu; Khan, F.H. (Asian Journal of Chemistry, 2011)
The kinetics of oxidation of propionaldehyde by bromate in the absence of any surfactant has been studied and compared with the kinetic parameters observed in the presence of cationic surfactant of cetylpyridinium chloride (CPC). The observed rate law is: -d[BrO3 –] / dt = k′[Aldehyde][BrO3 –] where k′ is a complex function of [H+] and [CPC].